The Eleven Stages of University: How to Implement A Combination of Gamification-Board game-Metaverse-AI - Gamayanto, Indra; Sundjaja, Arta Moro; Mailangkay, Adele B L; Sirait, Tamsir Hasudungan (Media Jurnal Informatika, 2024)
AbstractTechnology is developing rapidly, and we need significant changes. One of them is the University. Universities are one of the pillars of the Country's progress, but not only this, the most basic level of education, from elementary school to higher levels, requires change. If we do not change and open our minds and eyes to change, we will not be able to deal with this long-term. Therefore, this concept research was done, and one of the most important reasons is "a significant change in all the ways we educate." This research is a development of the concept of the seven stages of maturity level inside a University, which is the basis for developing the next idea, namely the new average University, which consists of eight stages. In researching this concept, we will go through eleven stages, starting from gamification (step nine), board game (step ten), and metaverse (stage eleven).Further research has continued. There is still the final stage to complete this concept, which we will make after this research is thorough. The results of this study are the framework and the maturity level of University Profiling 2.0, which will become the basis for implementing gamification, board games, and metaverse in universities. They can even be applied in the most basic and advanced education. Remember: Change can only occur when human resources, habits/culture, and information technology/infrastructure are ready. We must keep these three things separate in building a high-quality education. Keywords: University, Education, Metaverse, Gamification, Board GameAbstrakTeknologi berkembang dengan pesat, dan kita membutuhkan perubahan yang signifikan. Salah satunya adalah Universitas. Universitas merupakan salah satu pilar kemajuan Negara, namun tidak hanya itu, jenjang pendidikan paling dasar, dari sekolah dasar hingga jenjang yang lebih tinggi, juga memerlukan perubahan. Jika kita tidak berubah dan membuka pikiran serta mata kita untuk perubahan, kita tidak akan mampu menghadapinya dalam jangka panjang. Oleh karena itu, penelitian konsep ini dilakukan, dan salah satu alasan terpentingnya adalah "perubahan yang signifikan dalam semua cara kita mendidik." Penelitian ini merupakan pengembangan dari konsep tujuh tahap tingkat kematangan dalam sebuah Universitas, yang menjadi dasar untuk mengembangkan gagasan selanjutnya, yaitu Universitas rata-rata baru, yang terdiri dari delapan tahap. Dalam meneliti konsep ini, kita akan melalui sebelas tahap, mulai dari gamifikasi (tahap kesembilan), permainan papan (tahap kesepuluh), dan metaverse (tahap kesebelas). Penelitian lebih lanjut terus dilakukan. Masih ada tahap akhir untuk melengkapi konsep ini, yang akan kita buat setelah penelitian ini tuntas. Hasil dari penelitian ini adalah kerangka kerja dan tingkat kematangan University Profiling 2.0 yang akan menjadi dasar penerapan gamifikasi, permainan papan, dan metaverse di perguruan tinggi. Bahkan, dapat diterapkan di jenjang pendidikan paling dasar dan tingkat lanjut. Ingat: Perubahan hanya dapat terjadi jika sumber daya manusia, kebiasaan/budaya, dan teknologi/infrastruktur informasi telah siap. Ketiga hal ini harus kita pisahkan dalam membangun pendidikan yang bermutu. Kata kunci:  Universitas, Pendidikan, Metaverse-AI, Gamifikasi, Permainan Papan